. A review of the current status of the Older A review of the current status of the Older Metamorphic Group and Older Metamorphic Tonalite Gneiss: insights into the Palaeoarchaean history of the Singhbhum craton, India - Hofmann, A.; Mazumder, Rajat (Geological Society, 2015)
The Older Metamorphic Group and the Older Metamorphic Tonalite Gneiss are classic examples of Palaeaoarchaean highgrademetamorphic rocks of the Singhbhum Craton of India. The Older Metamorphic Group is a supracrustal assemblage that was probably deposited as a greenstone belt-type succession before c. 3.32 Ga, the low-grade equivalents of which are found in parts of the Iron Ore Group. The Older Metamorphic Tonalite Gneiss represents a suite of granitoids that are tectonically interleaved with the supracrustal gneisses and that formed over an extended period of time, 3.53-3.45 Ga and possibly later, by processes of Archaean crustal growth.